KECEPATAN RAMBATAN GELOMBANG SUARA DAN KETEGUHAN LENTUR DINAMIS OSB (Oriented Strand Board) PADA BERBAGAI PANJANG STRAND DAN CAMPURAN 3 JENIS BAMBU - Pamona Silvia Sinaga (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
This study evaluates the stress wave velocity (SWV) and modulus of elasticity dynamic (MOED) in different length of strands and three species of bamboo. The variables of this study consisted of a combination of three species of bamboo and variation of strands length. Bamboo that used are bamboo Andong, Betung, and Ampel with the code of each row are G, B, and L. The combination made in an OSB board consists of two types of bamboo that is one kind of bamboo for the face and back layers, and one species of bamboo again to core layer ratio of face, core, and back row 1:2:1. OSB board is made with nine combinations of GGG, BBB, LLL, GBG, GLG, BGB, BLB, LBL and LGL with strands length are 7 cm, 10 cm, and 13 cm. The parameters observed included stress wave velocity, modulus of elasticity dynamic in wet and dry conditions state in parallel and perpendicular direction.The results revealed that strand combination showed significant effect on all boards parameters (SWV, MOED in wet and dry conditions state in parallel and perpendicular direction). The results of OSB from Betung and Andong produces the best quality when compared with the characteristic of OSB properties to Ampel’s OSB. Different length of strand showed significant effect on all boards except MOED in wet and dry state perpendicular direction. The results indicated that OSB made from different length of strand showed that the higher length of strand (13 cm) produces a better OSB.